Crop Stress Management and Global Climate Change - Araus, José Luis (CABI, 2014)
This book addresses the challenges of the foreseen climate change for agriculture from a multidisciplinary point of view. Agriculture has shaped the world into its present form. It was only after the beginning of agriculture, and the relative food security and sufficiency thereby derived, that after 120,000 years populations have increased substantially, giving place to complex social structures created by civilization. Interestingly, the 'Neolithic revolution' (i.e. the agricultural revolution determining the transition from hunting- gathering to settlement facilitated by the beginning of agriculture) took place somewhat simultaneously in several different parts of the world. It should have been a global force determining such a change in culture. A remarkable feature is that this 'revolution' was temporally coincident with the occurrence of sudden climate changes that, unlike those expected nowadays, determined an increase in humidity which, in turn, determined a climate amelioration for crop growth in the early Holocene. Therefore, in this book the initial chapter is devoted to discussing the global changes that, some 10,000 years ago, gave rise to the beginning of agriculture. The rest of the book is subdivided in two major parts: first, towards an understanding of the present and future challenges imposed by climate change on several different agricultural systems; and, secondly, to reviewing research avenues to cope with the environmental conditions expected in the near future from climate change.